Exp-Kumaraswamy Distributions: Some Properties and Applications - Z. Javanshiri; A. Habibi Rad; N.R. Arghami (Journal of Sciences, Islamic Republic of Iran)
In this paper, we propose and study exp-kumaraswamy distribution. Some of its properties  are derived, including the density function, hazard rate function, quantile function, moments,  skewness  and kurtosis.   Adata set isused to illustrate an application of the proposed distribution. Also, we obtain a new distribution by transformation onexp-kumaraswamy distribution.   New distribution is an alternative to skew-normal distribution. Basic properties ofthis new distribution, such as moment generating function, moments, skewness, kurtosis and maximum likelihood estimation are studied. Its applicability is illustrated by means of two real data sets.